Curcugreen Treatment Prevented Splenomegaly and Other Peripheral Organ Abnormalities in 3xTg and 5xFAD Mouse Models of Alzheimer's Disease - Jayeeta Manna; Gary L. Dunbar; Panchanan Maiti (MDPI AG, 2021)
Metabolic dysfunction and immune disorders are common in Alzheimer's disease (AD). The mechanistic details of these epiphenomena in AD are unclear. Here, we have investigated whether a highly bioavailable curcuminoid formulation, curcugreen (CGR), can prevent abnormalities in peripheral organs of two mouse models of AD. Eighteen- and 24-month-old male and female 3xTg and 5xFAD mice were treated with CGR (100 mg/kg) for 2 months, orally. Cytoarchitectural changes of spleen, liver, kidney and lungs were studied by H&E stain. Apoptotic death was confirmed by TUNEL staining. Amyloid deposition, pTau levels, proinflammatory, anti-inflammatory and cell death/survival markers were studied by Western blots. Curcugreen reduced the observed splenomegaly (3xTg) and degeneration of spleen, granulomatous inflammation in the kidney, hepatic sinusoidal disorganization, hepatocellular hypertrophy, inflammation of the central hepatic vein, infiltration and swelling of lung tissues, and apoptotic death in all these areas in both 3xTg and 5xFAD mice. Similarly, CGR decreased amyloid deposition, pTau, proinflammatory markers, cell loss and decrements in anti-inflammatory markers in both 3xTg and 5xFAD mice. Peripheral organ abnormalities and inflammatory responses in AD were ameliorated by curcuminoid treatment.